2015
DOI: 10.1039/c4dt02893g
|View full text |Cite
|
Sign up to set email alerts
|

Anion complexation, transport and structural studies of a series of bis-methylurea compounds

Abstract: A new family of bis-methylureas () have been synthesised and their ability to bind anions both in solution and in the solid state and to transport them through lipid membrane have been studied. From the solid state studies it has emerged that various conformations can be adopted by the receptors allowing the isolation of complexes of different stoichiometries (from 1 : 1 to 1 : 3). The transport studies highlighted the possibility to use bis-methylureas to mediate Cl(-) transport across membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…The affinity is higher than those previously observed for similar systems . H 2 PO 4 − is also bound more strongly by 1 than by other compounds with the same binding motif …”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…The affinity is higher than those previously observed for similar systems . H 2 PO 4 − is also bound more strongly by 1 than by other compounds with the same binding motif …”
Section: Resultscontrasting
confidence: 49%
“…The measureda ffinitiesa re one to two orders of magnitude higher than those for comparable systems under the same conditions. [3e19, 21,22,24] Considering tetrahedral anions, SO 4 2À is very strongly bound by 1,a so ften found for this substrate. [3d] Indeed the 1 HNMR experimentsi ndicatet he binding of as econd anion to form 1·(SO 4 2À À ) 2 ,d espite the Coulomb repulsion between the two anions.…”
Section: Affinities For Anions In Solution By Nmr Spectroscopymentioning
confidence: 68%
See 1 more Smart Citation
“…Olivari et al 84 reported a series of bismethylurea compounds 168-169 with aromatic substituents (Figure 57). Although both trifluoromethyl (CF 3 ) and nitro (NO 2 ) are electron-withdrawing groups, the fluorination from CF 3 substituents improves the lipophilicity of the compounds.…”
Section: Transmembrane Anion Transportmentioning
confidence: 98%
“…However, in this scenario, and, to the best of our knowledge, examples of selenourea-based anion sensors have never been reported in the literature to date despite selenoureas are interesting organoseleno compounds that show anticancer activity, antioxidant properties, enzyme inhibition, and DNA binding properties. [16][17][18][19][20] Taking these concepts into account and following our interest in anion recognition and sensing [21][22][23][24][25] we decided to explore the potential use of selenoureas as a new scaffold for the design of anion chemosensors.In particular, here, we describe the ability of the asymmetric 1-(4-methyl-2-oxo-2H-chromen-7-yl)-3-phenylselenourea (L) to act as a colorimetric and/or fluorescent sensor for S 2-and CNrecognition. L was obtained according to the reaction shown in Scheme 1.…”
mentioning
confidence: 99%